Allogeneic HSCT in Adolescents and Young Adults With Primary Immunodeficiencies - Morris, Emma C.; Albert, Michael H. (Frontiers in Pediatrics, 2019)
Signiﬁcant advances in hematopoietic transplantation over the past 20 years, have facilitated the safe transplantation of older adults with higher co-morbidities. In pediatric practice these advances have simultaneously improved outcomes for sicker children with complex, rare diseases including the primary immunodeficiencies, PID. With more widespread adoption of genetic sequencing, older patients with disease-causing mutations restricted to the hematopoietic system can be identified who may benefit from allogeneic hematopoietic stem cell transplantation (Allo-HSCT). Here we discuss the evidence for Allo-HSCT in adolescent and younger adults (AYAs) with PID.